2013
DOI: 10.5251/ajfn.2013.3.3.105.116
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of banana wine fermented with recombinant wine yeast strains

Abstract: Commercial enzyme preparations are applied in the process of winemaking to improve wine processing and wine quality. In this study, three recombinant wine yeast strains that had been developed to improve wine processing were compared with regard to their ability to produce banana wine of an acceptable quality. The recombinant wine yeast strains contain genes coding for enzymes able to degrade different polysaccharides (glucan, xylan, pectin and starch). The recombinant strains were able to induce higher wine y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Other studies have found that different commercial enzymes improve banana pulp digestion, yields, and the clarity of juice and wine made from ( Musa acuminata ) bananas (Jackson & Badrie, 2002; Mabesa et al, 1989). Similarly, Byarugaba‐Bazirake & Rensburg (2013) compared the control wine with enzyme‐treated wine and the wine turbidity was lowered significantly in the wines prepared from juices that were extracted from commercial enzyme‐treated pulps.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have found that different commercial enzymes improve banana pulp digestion, yields, and the clarity of juice and wine made from ( Musa acuminata ) bananas (Jackson & Badrie, 2002; Mabesa et al, 1989). Similarly, Byarugaba‐Bazirake & Rensburg (2013) compared the control wine with enzyme‐treated wine and the wine turbidity was lowered significantly in the wines prepared from juices that were extracted from commercial enzyme‐treated pulps.…”
Section: Resultsmentioning
confidence: 99%
“…When selecting an enzyme for an industrial process, enzyme specificity is critical. An enzyme with optimum activity above pH 3 must be chosen for best enzyme efficiency (Byaruagaba‐Bazirake & Rensburg, 2013).…”
Section: Resultsmentioning
confidence: 99%